Trends of homicidal deaths in central Bangkok, Thailand: a 5-year retrospective study - Vorada Sakulsaengprapha (2019)
© 2018, The Author(s). Background: The aim of this study was to analyze the trends related to homicide victims in central Bangkok, Thailand. These trends were analyzed in terms of general figures and demographics, as well as case-specific details such as time, day, month, weapon, cause of death, location of injury and toxicology. Data was collected using autopsy archives from 2009 to 2013 and specific details were recorded and analyzed statistically. Results: Major trends identified included generally decreasing rates of homicide, larger proportions of male victims, higher rates of homicide during the hotter months of the summer, and the most common weapon being firearms and sharp force. Also consistent with global trends is a majority of victims being unmarried. Unique to the Thai population, due to social and legal factors, included the frequency of firearm and sharp force injuries, as well as methamphetamine being the most common psychoactive substance found in victim toxicology. Furthermore, many unique points, such as the correlation between the cause of death and the type of force, were made. Conclusions: Several characteristics of homicide that are similar to global trends have been found in this study. However, some trends were found differed from other countries included the anthropometric data, the types of forces and its relationship to location, as well as which psychoactive substances were detected.